Prevalence of r5 and x4 Hiv Variants in Antiretroviral Treatment Experienced Patients with Virologic Failure - Beltran-Buendia, C; Tello-Reyes, M (Elsevier, 2014)
Background: Antiretroviral therapy (ART) inhibits virus replication. Nevertheless, ART has the disadvantage of generate selective resistance and adverse events. Coreceptor antagonists are a family of antiretroviral drugs that are used with the prior knowledge of patients HIV tropism. Objectives: The purpose of this work was to estimate the prevalence of R5 and X4 variants among Chilean patients under antiretroviral therapy and virological failure and investigate variables such as plasma viral load (pVL) and CD4 cell count in the population studied. Study design: HIV RNA or proviral DNA was extracted from 454 consecutives patients and tropism testing was performed using a genotypic method performed with Geno2pheno setting a cutoff value for FPR 5.75%. Results: Among 454 individuals analyzed, 299 (66%) harbouring exclusively R5 variants. They not displayed a better clinical profile than individuals harbouring X4 strains (22%). For R5 patients the median of pVL and CD4 cell count were 268,000. copies/mL, and 223. cells/?L respectively. For X4 samples the values were 368,000. copies/mL and 214. cells/?L [. P>. 0.05]). Only, 53 patients (12%) could not be analyzed and were categorized as non-reportable. Conclusions: The genotypic method confirmed that R5 strains were more prevalent despite the fact that patients were treatment-experienced for several years. The genotypic strategy proved to be a faster and cost-effective option as compared to phenotypic assays. According to our results, two of every three patients under antiretroviral therapy and with virologic failure harbour R5 strains, and may be candidates for use of a CCR5 antagonist. © 2014 Elsevier B.V.